Genetic parameters for milk yield analyzed by test-day models in Murrah buffaloes in Brazil - Humberto Tonhati (Italian Journal of Animal Science, 2010)
New statistical models for genetic parameters estimation based on longitudinal data have being proposed. In this study, information of 47,614 test day milk yield data from 1.578 buffaloes, with 4.757 complete lactation, which calves from 1985 to 2006, were considered. Single-, two- and multiple trait analyses were used and variance components were estimated by Restricted Maximum Likelihood. The model used to evaluate the milk yield at 305 days (MY305) trait included herd-year-calving season (contemporary group) and milking number as fixed effects, buffalo age at calving was considered as covariate (linear and quadratic effect) and additive genetic, permanent environmental, residual and the animal were considered random effects. The same effects were included in the test day milk yield model except the contemporary group defined as herd-year-test day month control. The heritability estimations for TDMY vary from 0.13 to 0.23 for single-trait analyses, from 0.13 to 0.24 for two-trait analyses and from 0.15 at 0.24 for the multiple-trait analyses. According to the three models analyzed, the higher heritability estimations were obtained in the third test month for all of them. The genetic correlations between the TDMY and MY305 were high and positive. In conclusion, the selection for TDMY trait will promote genetic changes to the same direction for MY305.